Senegalia lotterii (Fabaceae) a new species endemic to the Barberton Centre of Endemism, South Africa - Hahn, Norbert (Phytotaxa, 2013)
Senegalia lotterii is a proposed new species to science, characterized by its paired prickles pointing straight ahead or slightly upwards one of which is often lost due to malformation. This species was found to be a distinct edaphic entity, endemic to the Barberton Centre of Endemism.